SME's Development: Is The Role of Women and Entrepreneurial Marketing Important? Case Study of Confection SME's in Jepara Indonesia - Nasihin, Ahmad Khoirun; Sarma, Ma’mun; Mintarto Munandar, Jono (School of Business, IPB University (SB-IPB), 2023)
Micro, Small, and Medium Enterprises (MSMEs) substantially contribute to the Indonesian economy. The marketing approach using entrepreneurial marketing is an appropriate approach to apply to MSMEs. This study aims to analyze the influence of the role of women and entrepreneurial marketing on the development of MSMEs confection businesses in Jepara Regency. The data collection method used a purposive sampling technique, namely the sampling technique, by distributing questionnaires to 137 respondents. While the analysis used is a descriptive quantitative analysis and Structural Equation Modeling (SEM) analysis through the Partial Least Squares (PLS) approach. The results showed that the characteristics of women entrepreneurs, in general, have a high school level of education, the majority of respondents are of productive age, have high morale, and are a generational group born in an era of rapidly developing technological developments. The results of the PLS-SEM analysis show that the role of women has a significant and positive effect on entrepreneurial marketing. This means that the better the encouragement of the role of women, the more entrepreneurial marketing will increase. In addition, the role of women has a significant and positive effect on business development. This means that the better the role of women, the more it will increase in business development. The analysis results on entrepreneurial marketing variables have a significant and positive effect on business development. This means that the better the entrepreneurial marketing drive, the more it will improve the development of MSMEs businesses in confection businesses in Jepara. Keywords: confection, entrepreneurial marketing, MSMEs development, PLS, women entrepreneurs